2023
DOI: 10.1002/ecs2.4333
|View full text |Cite
|
Sign up to set email alerts
|

Lakescape connectivity: Mobile fish consumers link Lake Michigan coastal wetland and nearshore food webs

Abstract: In large lake ecosystems, fish movement between coastal littoral habitats such as wetlands and the adjacent open-water nearshore represents an understudied but potentially important linkage supporting energy flow and fisheries production. We hypothesized that yellow perch (Perca flavescens), an ecologically and economically important sport fish in the Laurentian Great Lakes, transport energy from highly productive wetlands to nearshore food webs, but that their role changes with ontogenetic shifts in diet and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…Ambient water isotope patterns presented herein are generally consistent with past studies in nearshore Lake Michigan (e.g., Jasechko et al 2014; Foley et al 2017, 2022; Senegal et al 2020) and with relatively few available studies that have simultaneously considered tributaries (e.g., Dufour et al 2005; Jameel et al 2018; Senegal et al 2020; O'Reilly et al 2023). Similar to δ 13 C in prey samples, δ 2 H and δ 18 O values in the ambient water followed a general trend of relatively low δ 2 H and δ 18 O values in tributaries and isotopic enrichment in nearshore Lake Michigan waters (e.g., Foley et al 2022).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Ambient water isotope patterns presented herein are generally consistent with past studies in nearshore Lake Michigan (e.g., Jasechko et al 2014; Foley et al 2017, 2022; Senegal et al 2020) and with relatively few available studies that have simultaneously considered tributaries (e.g., Dufour et al 2005; Jameel et al 2018; Senegal et al 2020; O'Reilly et al 2023). Similar to δ 13 C in prey samples, δ 2 H and δ 18 O values in the ambient water followed a general trend of relatively low δ 2 H and δ 18 O values in tributaries and isotopic enrichment in nearshore Lake Michigan waters (e.g., Foley et al 2022).…”
Section: Discussionsupporting
confidence: 88%
“…Mixing model outputs showed that all three fish species, including less mobile round goby, integrate a variety of resources across Muskegon habitats. Resource exchange indicates that Muskegon habitats are likely interconnected due to the physical characteristics of this system (Essig 2016; O'Reilly et al 2023) and that fish may move between these habitats for feeding and refuge. In addition, based on isotopic variation in bivalve shells, Muskegon Channel may be an important convergence zone for fish between the productive Muskegon Lake and nearshore Lake Michigan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These spatial perspectives on landscape ecological properties apply to inland aquatic systems. In lakes and ponds, coastal wetlands and littoral and offshore zones are characterized by unique biological communities and resource and animal movements across them (Schoen et al, 2016; O’Reilly et al, 2023) whereas riparian zones along the shore interact with aquatic compartments through ecosystem subsidies (Gratton et al, 2008; Francis & Schindler, 2009; Jonsson & Wardle, 2009). Similarly, in rivers, hierarchically nested habitats range from microhabitats in pools and riffles to river segments within an upstream-downstream continuum (e.g., Poole, 2002; Gurnell et al, 2016).…”
Section: Introductionmentioning
confidence: 99%